พฤติกรรมการบริโภคอาหารและระดับความดันโลหิตของผู้ป่วยโรคความดันโลหิตสูงที่มารับบริการในโรงพยาบาลแม่แตง - ธีรวัฒน์ บุญชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2019)
The objectives of this study were to study food consumption behavior and blood pressure level among hypertensive patients received services in Maetang Hospital, Chiang Mai Province. The sample was composed of 210 patients who received services at the hypertension clinic. The data were collected in the day of service by using structured interviews about food consumption behavior for the last one week. The content validity verified by three experts. The result of IOC range from 0.66 to 1.00 and the reliability by calculating the coefficient of Cronbach alpha was 0.91. The data were analyzed and presented in percentage, mean and standard deviation. The study indicated that the hypertensive patients had optimal consumption behavior at high level. The food items, which the patients had optimal food consumption behavior at low level, included monosodium glutamate/seasoning foods, reduced seasoning salty foods, low fat foods, cooked brown rice and steamed sticky rice. Regarding blood pressure levels, the controlled hypertensive patients had an estimated 62.41 % to 74.90 % and it was found that the percentages of uncontrolled hypertensive patients increased by the time it was diagnosed. In addition, the patients who were diagnosed with hypertension in a period of 16-25 years, mostly male, aged 60 years and over.